2000
DOI: 10.1007/pl00010059
|View full text |Cite
|
Sign up to set email alerts
|

A Brief Course of Colon Preparation with Oral Antibiotics

Abstract: We carried out a prospective clinical trial of colon preparation with a regimen of oral antibiotics starting on the day before surgery. The patients were assigned to one of two groups consisting of either a mechanical preparation alone group (group 1, 45 cases) or a mechanical bowel preparation with oral antibiotics group (group 2, 38 cases). Group 2 received kanamycin and metronidazole three times on the day before surgery. Cefmetazole was administered for 3 consecutive days as prophylaxis in both groups. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 15 publications
2
24
0
7
Order By: Relevance
“…It was observed that during study, the animals of this group had suffered from fever for three to four days that's why the gain in the tensile strength was lower than the groups having single dose of intravenous antibiotic prophylaxis. These findings are also inline with those of Athar et al, Cai (1992) , Leaper (1994), Lindhagen et al, (1981), Mittermayer et al, (1984) Ono et al, (1990) Parker et al, (1985 Playforth et al, (1988) and Takesue et al, (2000). As for the choice of antimicrobial agents, it is general consensus worldwide that administration of prophylactic antibiotics should be intravenous as single dose preferably 1 hour to 30 minutes before surgery.…”
Section: Discussionsupporting
confidence: 85%
“…It was observed that during study, the animals of this group had suffered from fever for three to four days that's why the gain in the tensile strength was lower than the groups having single dose of intravenous antibiotic prophylaxis. These findings are also inline with those of Athar et al, Cai (1992) , Leaper (1994), Lindhagen et al, (1981), Mittermayer et al, (1984) Ono et al, (1990) Parker et al, (1985 Playforth et al, (1988) and Takesue et al, (2000). As for the choice of antimicrobial agents, it is general consensus worldwide that administration of prophylactic antibiotics should be intravenous as single dose preferably 1 hour to 30 minutes before surgery.…”
Section: Discussionsupporting
confidence: 85%
“…The overall incidence of surgical site infection (5.8%) in this study is considered identical to or lower than those recently reported [16][17][18] from Japan. There has been only one report other than this study that has assessed the method of perioperative antimicrobial prophylaxis according to CDC guidelines.…”
Section: Discussionsupporting
confidence: 61%
“…2). The 16 studies included in the meta-analysis are outlined in Table 1 [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. No eligible trial was found prior to 1980, and the first trial included in the SWI meta-analysis was from 1982.…”
Section: Resultsmentioning
confidence: 99%